Mental health of Ukrainian researchers during wartime - Natalia Tsybuliak; Anastasia Popova; Hanna Lopatina; Yana Suchikova (Global Public Health)
The full-scale war in Ukraine has introduced unique challenges for researchers, including physical displacement, destruction of research infrastructure, and deteriorating working conditions. This qualitative study investigates the impact of the ongoing war on the mental health and academic functioning of Ukrainian researchers. Based on 30 semi-structured interviews conducted between February and April 2024, the study reveals pronounced psychological consequences, including stress, anxiety, burnout, and feelings of isolation. Academically, researchers reported significant disruptions in research productivity, loss of professional networks, and diminished institutional support. Three critical areas of impact were identified: (1) the deterioration of working conditions and researcher well-being, (2) the fragmentation of academic communities and networks, and (3) restricted access to research resources and support. Despite these challenges, many researchers demonstrated resilience by adapting to remote work, forming new international collaborations, and finding renewed purpose in contributing to Ukraine’s recovery through science. The findings underscore the urgent need for comprehensive, multilevel support systems that include mental health services, financial and infrastructural assistance, and initiatives to restore academic belonging. These insights are essential for developing responsive strategies to support academic communities in crisis settings globally.